(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Assessing family communication is important for understanding relationship dynamics and identifying areas for improvement. This article reviews various forms of evaluation that can be applied, including observation, interviews, exercises and assessments. Specific methods are discussed like checking emotional check-ins, problem-solving discussions and quality time activities. Details are provided on how to measure constructs like vulnerability, empathy and cooperation. The forms of assessment outlined offer researchers and clinicians structured approaches to capture the nuances of family interaction and pinpoint strengths or weaknesses in exchanges.